Cation Exchange Protocols to Radiolabel Aqueous Stabilized ZnS, ZnSe, and CuFeS2 Nanocrystals with 64Cu for Dual Radio‐ and Photo‐Thermal Therapy. (26th May 2020) - Avellini, Tommaso; Soni, Nisarg; Silvestri, Niccolò; Fiorito, Sergio; De Donato, Francesco; De Mei, Claudia; Walther, Martin; Cassani, Marco; Ghosh, Sandeep; Manna, Liberato; Stephan, Holger; Pellegrino, Teresa
Abstract: Here, cation exchange (CE) reactions are exploited to radiolabel ZnSe, ZnS, and CuFeS2 metal chalcogenide nanocrystals (NCs) with 64 Cu. The CE protocol requires one simple step, to mix the water‐soluble NCs with a 64 Cu solution, in the presence of vitamin C used to reduce Cu(II) to Cu(I). Given the quantitative cation replacement on the NCs, a high radiochemical yield, up to 99%, is reached. Also, provided that there is no free 64 Cu, no purification step is needed, making the protocol easily translatable to the clinic. A unique aspect of the approach is the achievement of an unprecedentedly high specific activity: by exploiting a volumetric CE, the strategy enables to concentrate a large dose of 64 Cu (18.5 MBq) in a small NC dose (0.18 µg), reaching a specific activity of 103 TBq g −1 . Finally, the characteristic dielectric resonance peak, still present for the radiolabeled 64 Cu:CuFeS2 NCs after the partial‐CE reaction, enables the generation of heat under clinical laser exposure (1 W cm −2 ). The synergic toxicity of photo‐ablation and 64 Cu ionization is here proven on glioblastoma and epidermoid carcinoma tumor cells, while no intrinsic cytotoxicity is seen from the NC dose employed for these dual experiments. Abstract : The first examples of cation exchange reactions used for quantitative radiolabelling with 64 Cu aqueous stable metal chalcogenides of ZnSe, ZnS and CuFeS2 nanocrystals are reported here, setting protocols readily transferable to the clinic. The exploitation of radiolabeled nanocrystals for dual therapy combining internal radiotherapy and phototherapy is also demonstrated.